EFFECT OF RECENTRIFUGATION ON THE LEVELS OF HIGH SENSITIVITY TROPONIN I - Nida, Sumbal; Afzal, Raja Kamran; Saeed, Mohammed Zaheer Us (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the levels of high sensitivity troponin I in plasma after specimen re-centrifugation in patients presenting with acute coronary syndrome. Study Design: Cross sectional study. Place and Duration of study: Department of Pathology, Armed Forces Institute of Cardiology, Rawalpindi, from Sep to Nov 2017. Material and Methods: Seventy five patients’ plasma samples of high sensitivity troponin I levels, exceeding the value of 0.06ng/ml were analyzed. Blood was collected in K/EDTA evacuated tubes and plasma was separated after an initial centrifugation (2000 g, 10 min; not refrigerated). The samples were recentrifuged after first analysis. High sensitivity troponin I was measured through the chemiluminescence technique on ADVIA CENTAUR XP immunoassay analyzer. Normally distributed continuous variables were presented as Mean ± SD and the others as median. Two-tailed Wilcoxon analysis was applied to determine the difference in high sensitivity troponin I specimens before and after recentrifugation. A p-value <0.05 was considered as statistically significant. Results: Median value of high sensitivity troponin I was 4.051ng/ml before re-centrifugation and 3.689 ng/ml after recentrifugation. About 2.5th to 97.5th percentile interval was 0.020-47.23 and 0.054-48.7 ng/ml, before and after recentrifugation, respectively. Difference between the two samples were statistically analyzed by using twotailed Wilcoxon analysis that showed a statistically significant difference (p-value<0.01). Conclusion: Recentrifugation of specimens is followed by a significant reduction in high sensitivity troponin I levels which may result in misdiagnosis and treatment of the patients.